Factors Associated with the Occurrence of Pneumonia among Under-Five in the Working Area of Jatinegara District Public Health Center in 2023: A Case-Control Study - Kartika Wandini; Mela Agustina; Ratna Mutu Manikam; Wiwit Wijayanti; Ratih Agustin Prikhatina (Universitas Mohammad Husni Thamrin, 2025)
Pneumonia is the main killer of under five in the world, more than any other infectious disease. Low immunity of underfive can be caused by unexclusive breastfeeding, cigarette smoke, chronic diseases and others. This study aimed to determine the risk factors that influence the incidence of pneumonia at Jatinegara Subdistrict Health Center in 2023. A case control study was conducted using questionnaire as instrument which included Respondent Identity, Birth Weight hsitory, Exclusive Breastfeeding History, Immunization Status and Family Smoking Habits. As much as 88 underfive were included in this study by purposive sampling. Data were analyzed using descriptive statistic and logistic regretion. The bivariate analysis showed significant correlation between exclusive breastfeeding (p.value 0.006; OR 0.267), immunization status (p.value 0.000; OR 0.043), also smoking behavior (p.value 0.000; OR 46.467) with pneumonia, but not for the age of underfive (p.value 1.000), gender (p-value 1.000), and LBW history (p.value 0.058). Multivariate analysis showed that there was an influence of immunization status and the incidence of pneumonia (p-value 0.021; OR 0.130) also smoking behavior of the family to the incidence of pneumonia at the Jatinegara Subdistrict Health Center (p-value 0.000; OR 27.122), While age, gender, birth weight, and exclusive breastfeeding had no effect on the incidence of pneumonia (p.value>0.05). It is recommended that the community be able to increase awareness of healthy behaviors such as not smoking in the house or environment.